1029. Long-Term Patient Adherence and Management of Treatment Interruptions With Long-Acting Injectable Cabotegravir + Rilpivirine for Maintenance Therapy in Phase IIb/III Studies. (31st December 2020) - Teichner, Paula; Wu, Sterling; Zhang, Feifan; Dorey, David; D'Amico, Ronald; Griffith, Sandy; Sutton, Kenneth; McCoig, Cynthia C; Upadhyay, Ojesh R; Polli, Joseph; Margolis, David; Van Solingen-Ristea, Rodica; et al.
Abstract: Background: Cabotegravir (CAB) and rilpivirine (RPV) are under development as a novel long-acting (LA) regimen for maintenance of HIV virologic suppression. Pooled data from pivotal phase III trials demonstrated noninferiority of CAB + RPV LA given as gluteal intramuscular injections vs current antiretroviral regimen (CAR) on the primary endpoint of HIV-1 ribonucleic acid (RNA) ≥50c/mL at Week 48, with high levels of adherence. Long-term adherence to dosing visits and outcomes after use of oral CAB+RPV to cover planned missed injections in FLAIR through Week 96 and in LATTE-2 through Week 256 is reported here. Methods: Virologically suppressed participants (HIV-1 RNA < 50c/mL) were randomized to switch to CAB+RPV LA or to continue CAR. On-time injections occurred every 4 weeks or every 8 weeks (LATTE-2 only) within a ±7-day dosing window of the projected dosing date. Adherence to LA therapy was calculated as the number of on-time injection visits divided by the number of expected dosing visits through the period of follow up. Injection visits outside the prespecified window and missed injection visits with or without use of oral dosing were characterized. Results: Of 6005 expected injection visits through Week 96 in FLAIR, 97% of injections were given within the allowed ±7-day dosing window, with 43% on the projected dosing date. 45 (< 1%) injection visits were early and 107 (2%) were late. Adherence to 9803 expected injection visits in LATTE-2, through Week 256, was similarly high, with 96% of injections given within the allowed ±7-day dosing window and 39% on the projected dosing date. For 31 missed injection visits in 18 participants across both trials, 30 were covered with oral CAB+RPV, with all participants maintaining HIV-1 RNA < 50c/mL through the last study visit. In those participants who used oral CAB + RPV for planned treatment interruptions, 3 had repeat use on ≥2 separate occasions. Conclusion: Participants maintained high levels of long-term adherence to CAB+RPV LA, through 2-5 years of follow up, with 97% of injections given within the ±7-day dosing window in the FLAIR and LATTE-2 clinical trials. Oral CAB+RPV to cover planned missed visits provides an effective strategy to maintain virologic suppression during short periods of LA treatment interruption. Disclosures: Paula Teichner, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Sterling Wu, PhD, GlaxoSmithKline (Employee, Shareholder) David Dorey, MMATH, GlaxoSmithKline Inc. (Employee, Shareholder) Ronald D'Amico, DO, MSc, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Sandy Griffith, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Kenneth Sutton, MA, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Cynthia C. McCoig, MD, ViiV Healthcare (Employee) Joseph Polli, PhD, FAAPS, ViiV Healthcare (Employee) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Rodica Van Solingen-Ristea, MD, Janssen R&D (Employee) Kati Vandermeulen, M.SC., Janssen Pharmaceutica (Employee, Shareholder) William Spreen, PharmD, ViiV Healthcare (Employee, Shareholder) Parul Patel, PharmD, ViiV Healthcare (Employee)